English Language Role in Higher Education Student Exchange Programs - Juan Arroba Muñoz; Judith Pinos Montenegro; Julio Zurita Altamirano (Revista Internacional de Cooperación y Desarrollo)
This paper aims to analyze scientific research related to the role of English language in higher education student exchange programs. For this purpose, data was collected through the use of scientific documentation from the Scopus database using a bibliometric analysis of results. The keywords “student mobility”, “higher education”, and “role of English” resulted in 38 documents related to the topic of study.  For the bibliometric analysis of results, this research focused on the number of documents per year, documents per country or territory, documents by subject, documents per funding sponsor, and documents by type as delineated in the Scopus search tool. The results showed that the country with the highest number of scientific studies in this area was the United Kingdom (nine publications), followed by Spain (five publications), and the United States (four publications) between 2005 until 2024, which highlighted the role of the English language as a medium of instruction in student exchange programs at higher education institutions. Further, a higher rate of article production was evident between 2019 and 2021. This led to the conclusion that English language knowledge, educational policies, college prestige, and scholarship sponsorship favorably impact student exchange programs.